Magnetically Actuated Tunable Soft Electronics - Ilami, Mahdi (ACS Omega, 2019)
[Image: see text] Variable electronics are vital in tunable filters, transmitters, and receivers, among other applications. In addition, the ability to remotely tune soft capacitors, resistors, and inductors is important for applications in which the device is not accessible. In this paper, a uniform method of remotely tuning the characteristic properties of soft electronic units (i.e. inductance, capacitance, and resistance) is presented. In this method, magnetically actuated ferrofluid mixed with iron powder is dragged in a soft fluidic channel made of polydimethylsiloxane (PDMS) to tune the electrical properties of the component. The effects of position and quantity of the ferrofluid and iron powder are studied over a range of frequencies, and the changes in inductance, capacitance, resistance, quality factor, and self-resonance frequency are reported accordingly. The position plays a bigger role in changing inductance, capacitance, and resistance. With the proposed design, the inductance can be changed by 20.9% from 3.31 μH for planar inductors and 23% from 0.44 μH for axial inductors. In addition, the capacitance of capacitors and impedance of resistors can be changed by 12.7% from 2.854 pF and 185.3% from 0.353 kΩ, respectively. Furthermore, the changes in the inductance, capacitance, and resistance follow “quasi-linear profiles” with the input during position and quantity effect experiments.